The Construction Of Digital Norm Ontology And The Functional Dynamics Of The Strategic Role Of Public Relations In VCoP - Megawati, Nur Afrila; Lawanda, Ike Iswary; Susetyo-Salim, Tamara Adriani (Communication, 2026)
Virtual Communities of Practice (VCoP) in the era of digital transformation have become a strategic asset for organizational knowledge management. Public relations play a crucial role as communication managers; however, operational standards integrating digital norms remain fragmented. Public relations play a crucial role as communication managers, but operational standards that integrate digital norms into this role remain fragmented. This study aims to build an ontology model capable of mapping the structure of digital norms. It also seeks to define the functional dynamics of public relations' role in moderating knowledge flows in a VCoP. This study uses an ontology engineering methodology consisting of the stages of specification, knowledge acquisition, conceptualization, logic formalization, and evaluation. Knowledge is acquired from the literature on knowledge management, digital citizenship, and strategic communication theory. This model is formalized using predicate logic in the form of axioms to describe interactions between entities. This study produces an ontology model consisting of four main classes: actors, digital norms, knowledge activities, and information assets. The functional dynamics of this model are mapped through five main axioms, three of which define the role of public relations. These axioms include the role of gatekeeper through the validity axiom, law enforcer through the legal intervention axiom, and facilitator through the social stimulation axiom. The evaluation results show that this ontology is able to answer competency questions related to information governance in virtual communication. This mapping proves that the role of public relations is shifting from mere moderators to information architects who ensure the security and credibility of organizational knowledge. Practically, this model can be adopted by organizations as a logical basis for developing decision support systems in community moderation and the preparation of structured ethical guidelines.